Socio-demographic Profile of Patients Admitted in Thalassemia Care Center of Chattogram Maa Shishu-O-General Hospital - Barua, Tanuka; Das, Aparup Kanti; Sultana, Razia; Das, Dhananjoy; Arju, Mahmood A Chowdhury (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: Thalassemia is the most common hemoglobin disorder in the worldincluding Bangladesh. Population migration and intermarriage between differentethnic groups have had a major impact on disease epidemiology. To observe theprevalence and specturm of thalassemia as well as demographic and social factorsof thalassemia patients. Materials and methods: This descriptive cross-sectional study was conducted in theThalassemia Care Center of Chattogram Maa Shishu-O-General Hospital,Chattogram from July, 2013 to June, 2014. Parents of 70 thalassemia patients aged2-18 years interviewed with a formulated questionnaire based on social anddemographic characteristics. Data were analyzed by both manually and by SPSS-18. Results: Mean age of patients was 6 years (± 3.66). Near about half of patients(40%) were diagnosed at the age less than 5 years. Mean age of diagnosis was 1.6years (± 1.53 SD). Majority of patients belonged to lower middle class (42.9%) withmale predominance (62.9%). A good number of patients (22.8%) were not engagedin any educational activity. Mean annual income of family was 262000 taka/year ±245477.35 (USD 3324.87 ± 3115.19). Mother contributed to annual income in only4.7% families. The percentage of Hb E/b thalassemia was the highest (54.4%)followed by b thalassemia major (37.1%) and Hb E disease (4.3%). Malepredominance was found in every type of thalassemia. Half of the thalassemiamajor patients were diagnosed during infancy and majority (60.53%) of Hb E/bthalassemia patients were diagnosed at the age less than 5 year. Conclusion: A nation-wide screening program should be carried out to address thecarrier status of population at risk. There may be further analysis regarding clinicaldiversity of thalassemia. Chatt Maa Shi Hosp Med Coll J; Vol.19 (1); January 2020; Page 33-37